2017
DOI: 10.5539/cis.v10n3p29
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Decision Framework to Avoid Vendor Lock-in for Cloud SaaS Migration

Abstract: Cloud computing offers an innovative business model to enterprise for IT services consumption and delivery. Software as a Service (SaaS) is one of the cloud offerings that attract organisations as a potential solution in reducing their IT cost. However, the vast diversity among the available cloud SaaS services makes it difficult for customers to decide whose vendor services to use or even to determine a valid basis for their selections. Moreover, this variety of cloud SaaS services has led to proprietary arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A further review of the literature identified that this issue, often known as the vendor lock-in scenario, occurs very commonly in the cloud environment [79,80]. Opara-Martins [81] studied a decision-making framework to mitigate vendor lock-in risks in (SaaS) cloud migration. Vendor lock-in and switching costs have become two significant obstacles to the retirement of cloud-based ERP systems.…”
Section: Resistance Characteristic: Vendor Lock-inmentioning
confidence: 99%
“…A further review of the literature identified that this issue, often known as the vendor lock-in scenario, occurs very commonly in the cloud environment [79,80]. Opara-Martins [81] studied a decision-making framework to mitigate vendor lock-in risks in (SaaS) cloud migration. Vendor lock-in and switching costs have become two significant obstacles to the retirement of cloud-based ERP systems.…”
Section: Resistance Characteristic: Vendor Lock-inmentioning
confidence: 99%
“…Prior to presenting the proposed taxonomy, it is worthy to mention that the identification of elements and components of the categorization used is based on the critical review of key literatures in [40][41][42][43][44][45], the preceding section and subsequent sections. This critical review followed the systematic approach proposed by [52].…”
Section: Classification Methodologymentioning
confidence: 99%
“…As cloud computing adoption rate soars across enterprises (small or large), the risks of vendor lock-in is prevalent. Limited studies exist, except for [40][41][42][43][44], to analyze and highlight the complexity of vendor lock-in problem in the cloud environment. Therefore, when selecting SaaS offerings from cloud vendors, organizations need to consider and balance service criticality against the significance of avoiding potential risks of vendor lock-in.…”
Section: Saas Lock-in Challengesmentioning
confidence: 99%
See 2 more Smart Citations